Pesantren Al-Kahfi Somalangu Kebumen Dalam Lintasan Revolusi - Adrianto, Bayu; Wijayati, Putri Agus (Journal of Indonesian History, 2020)
In 1945-1949, along with the development of the nationalism spirit of rejection of colonialism echoed by international institutions, which were transferred to countries in the world, including Indonesia. The return of the Dutch to occupy Indonesia, the spread of the spirit of patriotism in various regions spearheaded by the military and the army of the people. One of them is the resistance carried out by the Islamic laskar of Somalangu Al-Kahfi Islamic Boarding School. The Islamic Warriors, named the Islamic Oemat Force (AOI), guarded the Kebumen area and the capital of Yogyakarta from the Dutch attack. The results of the study showed that the role of the AOI as an Islamic army which had its headquarters in Al-Kahfi Somalangu Islamic Boarding School was quite large during military aggression. they commanded with the military trying to defend Kebumen from the Netherlands. Not only that, the contribution was also carried out in maintaining the Republic of Indonesia's capital, Yogyakarta. After the KMB diplomacy, the fusion of paramilitary forces and military forces became a part of APRIS, apparently not ready. This can be seen after the clash between groups, which resulted in civil war.